Responders and nonresponders after catheter ablation procedure and antiarrhythmic drug therapy in patients with paroxysmal AF: data from implantable cardiac monitors - А. А. Симонян; В. Н. Колесников; Л. И. Виленский; Ю. С. Кривошеев; Д. И. Башта; М. Ю. Гатило; Т. А. Мызникова; З. А. Мисходжева (Патология кровообращения и кардиохирургия, 2016)
Aim. The aim of this study was to assess the number of responders and nonresponders after catheter ablation procedure and antiarrhythmic drug therapy (AAD) in patients with paroxysmal AF through implantable cardiac monitors (ICM). Methods. 92 patients with paroxysmal AF were randomized into two groups: 1) AAD + ICM implantation (group I; n=46), and 2) AF catheter ablation (CA) + ICM implantation (group II; n=46), and 2). Patients with an AF% < 0.5% were considered AF-free (responders). Patients with AF% > 0.5% were classified as nonresponders. The follow up of this study was 24 months. Results. At the end of the follow-up period 13 (28.3%) patients in AAD group and 29 (63 %) patients in CA group were responders (log-rank test; р=0.0009; HR 2,6; 95% CI [1.44-4.69], р=0.001, Cox regression). According to multivariate logistic regression analysis data, AF burden>4.5% during the first two months after treatment (odds ratio [OR]=38,9; 95% confidence interval [CI], 6.2–245; P<0.001), arterial hypertension (OR=12.7; 95% CI, 1.9–85.3; P=0.009) and AF duration more than 5 years (OR=8.5; 95% CI, 1.04–69.6; P=0.044) were independent predictors of AF burden progression Conclusion. According to implantable cardiac monitors data, in patients with paroxysmal AF radiofrequency catheter ablation as compared to antiarrhythmic drug therapy results in higher percentage of responders. Received 10 July 2016. Accepted 22 August 2016. Funding: The study had no sponsorship. Conflict of interest: The authors declare no conflict of interest.